Novel robust observer‐controller synthesis method for Takagi‐Sugeno systems. Issue 4 (6th March 2020) - Xie, Wen‐Bo; Zheng, Hua; Li, Ming‐Yang; Shen, Mou‐Quan
Abstract: For the output feedback control problem of a T‐S fuzzy system, an H ∞ observer‐controller synthesis method is proposed. First, with parallel distributed compensation fuzzy observer and controller, an augmented error system is obtained. Based on Lyapunov function approaches, system stability and robust conditions are achieved. Then, by dividing the non‐convex conditions into observer‐dominant and controller dominant parts, the conditions are converted into convex form to facilitate the numerical solving process. Also, input saturation and system measurement disturbance are considered in the synthesis procedure. Finally, a numerical and a vessel control example are adopted to make comparisons with existing methods, with the results clearly showing the conservatism reduction effects and good control performance of the proposed method.